UI/UX Design Development for The SiCamar Application: A VR-Based Interactive Learning Media - Bayu Kurniawan; Wahyu Djoko Sulistyo; Listyo Yudha Irawan (UIN Fatmawati Sukarno Bengkulu, 2025)
The rapid advancement of technology significantly affects various life aspects, notably education. Virtual reality (VR) is a key technology that enables the creation of educational media for historical sites. However, previous research indicates limitations in features and accessibility. This study aims to develop a prototype application called SiCamar (Malang Raya Temple Site) based on VR. Using a research and development (R&D) approach, we applied the ADDIE model, focusing only on the Analysis, Design, and Development stages since the goal was to create a prototype and test its initial feasibility. The needs analysis revealed that users desired to experience the historical site via a VR platform. Essential features identified include 360-degree panoramas, videos, teaching materials, and maps, while necessary learning activities involve virtual tours, video observation, reading materials, and answering questions. In the design phase, the use of AI facilitated the creation of an attractive user interface. User testing results indicate that the SiCamar application effectively enhances user satisfaction, particularly in supporting the learning process.